Prognostic value of sarcopenia in patients with nasopharyngeal carcinoma: a meta-analysis - Xiaobin Gu; Yonggang Shi (Annals of Medicine, 2025)
Background Sarcopenia is widely explored for its significance for predicting nasopharyngeal carcinoma (NPC) prognosis, yet current results are inconsistent. Consequently, this meta-analysis focused on investigating its precise role in predicting NPC prognosis.Methods We systemically retrieved studies in PubMed, Web of Science, Embase and Cochrane Library from inception to 17 March 2025. Sarcopenia was analysed for its role in predicting overall survival (OS) and progression-free survival (PFS) in NPC through determining combined hazard ratios (HRs) and 95% confidence intervals (CIs). Thereafter, associations of sarcopenia with NPC clinicopathological factors were estimated through aggregating odds ratios (ORs) with 95%CIs.Results There were eight studies with 5458 cases enrolled in this study. Based on the aggregated findings, sarcopenia was remarkably related to unfavourable OS (HR = 1.88, 95% CI = 1.47–2.40, p < .001) as well as PFS (HR = 2.03, 95%CI = 1.48–2.80, p < .001) of NPC. Moreover, sarcopenia was significantly associated with higher T stage (OR = 1.33, 95%CI = 1.12–1.59, p = .002). But it was not related to gender (OR = 0.87, 95%CI = 0.42–1.77, p = .694), N stage (OR = 1.00, 95%CI = 0.87–1.16, p = .952) and tumour-node-metastasis (TNM) stage (OR = 1.17, 95%CI = 0.94–1.46, p = .153) in NPC.Conclusions This meta-analysis demonstrated that sarcopenia was a significant prognostic marker for poor OS and PFS in patients with NPC. Moreover, sarcopenia was also significantly associated with higher T stage of NPC.